A Preliminary Development of Baseline For Normal Condition of Local Exhaust Ventilaton System (Lev)By Using Mahalanobis Distance (Md) Method - Nuur Husna, Hasnin (2012)
Ventilation is the mechanical system in a building that brings in fresh outdoor air and removes the contaminated indoor air. In a workplace, ventilation is used to control exposure to airborne contaminants. It is commonly used to remove contaminants such as fumes, dusts, and vapors, in order to provide a healthy and safe working environment. Therefore, the LEV system is considered as an important system that should have in every single workplace so that all the workers are not exposed to the hazardous. In measuring the LEV systems, the study has come out with a new approach which is Mahalanobis Distance method (MD). It is believe that this new method is one of the first attempts to evaluate local exhaust ventilation performance by using multi-dimensional approach. The previous method of measuring the local exhaust ventilation system is time consuming which means it took a long period of time in order to measure the point. Besides, not all the measuring points give a significant value for the overall performance of local exhaust ventilation systems. The purposed of this study is to develop the preliminary baseline on normal conditions that will be a starting point on solving the time consuming problem on measuring the local exhaust ventilation systems.